PENERAPAN ANGGARAN FLEKSIBEL SEBAGAI ALAT PERENCANAAN DAN PENGENDALIAN BIAYA PRODUKSI PADA PT. ANSAR TERANG CRUSHINDO - Annisa Shabrina; Nur Khusniyah Indrawati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
Real sector investment require substantial capital and need a relatively long time to develop. One of the real sector investment is mining sector which is a capital-intensive industry so it is expected to grow innovative and competitive as well as get achievement of efficiency in the production activity. It have an important role because it is done repeatedly in a regular frequency and absorbs a lot of the cost of production. Therefore, budgeting such as planning and control production costs is needed. The research aims are to know planning and control of production costs and implementation of flexible budget as a tool for planning and control activity of production costs PT. Ansar Terang Crushindo. Research design is a descriptive. Data were collected by interview and documentation. Analysis of the research is comparing between budget and actual production costs as well as analysis of variances. The result show that the company uses a static budget as a basis of comparison realization of the company's production costs. Therefore, variance shows large difference and unfavorable. If flexible budget is used as a planning, variance production cost become smaller because is adapted by the realization of production volume. Implementation of flexible budget is used by splitting cost behavior pattern, separating of fixed and variable costs, and determining activities range. Keywords : Production costs, Flexible budget, Planning, and Control